THE EFFECT OF INTERNET BANKING SERVICE QUALITY ON CUSTOMER SATISFACTION LEVEL OF PT BANK MANDIRI (PERSERO) TBK KCP MEDAN KIRANA - Bertha Nerpy Siahaan (Jurnal Ekonomi, 2022)
The research entitled “The Effect of Internet Banking Service Quality on Customer Satisfaction of PT. Bank Mandiri (Persero) Tbk KCP Medan Kirana". This study aims to determine whether the quality of Internet Banking services affects the level of customer satisfaction at PT Bank Mandiri (Persero) Tbk KCP Medan Kirana. The data collection technique in this study was through a questionnaire. Data processing methods: Descriptive Analysis, Simple Linear Regression, Correlation Coefficient, and Coefficient of Determination. Based on the results of the regression equation y=0.52 – 0.88x, the Correlation Coefficient value of 0.68 means that the relationship between Internet Banking service quality and customer satisfaction is in the strong category, and the results of the calculation of the Coefficient of Determination; that 46